2016
DOI: 10.1002/ajh.24605
|View full text |Cite
|
Sign up to set email alerts
|

The role of acuity of illness at presentation in early mortality in black children with acute myeloid leukemia

Abstract: Black patients with acute myeloid leukemia (AML) experience higher mortality than White patients. We compared induction mortality, acuity of illness prior to chemotherapy, and insurance type between Black and White patients to assess whether acuity of presentation mediates the disparity. Within a retrospective cohort of 1,122 children with AML treated with two courses of standard induction chemotherapy between 2004 and 2014 in the Pediatric Health Information System (PHIS) database, the association between rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 43 publications
1
53
1
Order By: Relevance
“…The difference in age distribution observed among those patients who died is consistent with our previous finding that age is a confounder in the association between race and mortality. 9 Importantly, a number of the White patients who died had congenital heart disease or prematurity, while the profile of preexisting conditions for Black patients who died included asthma and autism (Table S1). The two most common causes of death in AML are hemorrhage and infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference in age distribution observed among those patients who died is consistent with our previous finding that age is a confounder in the association between race and mortality. 9 Importantly, a number of the White patients who died had congenital heart disease or prematurity, while the profile of preexisting conditions for Black patients who died included asthma and autism (Table S1). The two most common causes of death in AML are hemorrhage and infection.…”
Section: Discussionmentioning
confidence: 99%
“…Early deaths have previously been associated with low performance status, French–American–British type M4 and M5, hyperleukocytosis, thrombocytopenia, and older age . We recently demonstrated that induction mortality among Black children with AML was more than twice that of White children . This disparity was associated with increased frequency of multiorgan system failure and increased requirement for Intensive Care Unit (ICU) level resources within 72 hr of initial admission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient characteristics included age, sex, insurance type (private, public, or other), and time period of diagnosis (2004–2009 vs 2010–2014). ICU‐level resource utilization during the first 72 hours following admission for initial AML chemotherapy was also included as a covariate, where the timeframe was chosen a priori to evaluate clinical acuity at presentation rather than acuity resulting from chemotherapy toxicity . Acuity of presentation was categorized into three groups (none, 1 system, and ≥2 systems) based on the number of organ systems requiring ICU‐level resources within the first 72 hours of the diagnostic admission.…”
Section: Methodsmentioning
confidence: 99%
“…Each of these mechanisms may be relevant at different points in the treatment and posttreatment trajectory. Our previous study focused on early mortality in the initial induction period and the role of acuity at presentation . This study demonstrated that black patients have higher acuity prior to initiating chemotherapy, which substantially contributed to higher mortality during induction I.…”
Section: Introductionmentioning
confidence: 95%